Eff ect of the Treatment with Alpha-Macroglobulin on the Development of Experimental Pancreatitis - Di Loreto, Verónica Elina (2013)
Alpha-macroglobulins are proteinase inhibitors. Monofl uorophosphate increases alpha-macroglobulin levels in plasma, inducing a higher survival rate and lower pancreatic damage in rats with pancreatitis. The aim of this study was to evaluate the eff ect of alpha-macroglobulin on the development of pancreatitis. Pancreatitis was surgically induced in Sprague-Dawley rats divided into groups of 16 rats each and subjected to the following intravenous treatments for 3 days: Controls: pancreatitis without treatment, Enriched plasma: pancreatitis + alpha-macroglobulin-enriched plasma, Normal plasma: pancreatitis + plasma with normal levels of alpha-macroglobulin, Saline Solution: pancreatitis + saline solution, Purifi ed alpha-macroglobulin: pancreatitis + purifi ed alpha-macroglobulin. After 14 days pancreatic damage was assessed using a score that measures: edema, fi brin, neutrophils, mononuclear leukocytes, necrosis, vascular congestion, thrombosis, hemorrhage and fi brosis. Pancreatic damage decreased and the percentage of animals with pancreatitis was lower in enrichedplasma and purifi ed alpha-macroglobulin groups. We conclude that the intravenous administration of alpha-macroglobulins causes a reduction in the histological damage produced by pancreatitis.